Allowed and forbidden zones in a Lightning-strokes spatio-temporal differential space. (1st March 2022) - Ben Ami, Yuval; Altaratz, Orit; Koren, Ilan; Yair, Yoav
Abstract: In this work, we analyze time series of lightning strokes as detected by an LF/VLF network, over the Eastern Mediterranean during winter storms. The strokes' raw data is examined without pre-grouping it into flashes. A distance-versus-time differential space (termed dRvsdT) is introduced, examining the intervals between successive strokes. While it loses information on the strokes' exact time and location, it clusters common properties of the time and space intervals. The clusters on the dRvsdT space point on strokes within a flash (<1 s), strokes that occur almost simultaneously but in remote thunderclouds (located 10 s–100 s km away), the recharge time of a thundercloud (10 s of sec, a time-lag when strokes cannot occur), and counts of local and remote flashes. This method and its implications for flash determination and properties are universal and can be used for similar measurements around the globe.